2022
DOI: 10.18502/ijpa.v17i2.9540
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Protoscolicidal Effectiveness of Hypertonic Saline, Silver Nitrate, Ethanol, Using Sponge Pad Method and In-jecting into Fertile Hydatid Cysts

Abstract: Background: We aimed to evaluate currently protoscolices agents by using two methods including injection and impregnated sponges with protoscolices agents. Methods: Hypertonic saline 20%, silver nitrate 0.5% and Ethanol 96% were injected into sheep hydatid cysts. Then, after different exposure times (5, 10, and 15 min), the protoscolices were aspirated from the cyst and viability of the protoscolices were evaluated microscopically using vital staining. In the second part, the live protoscolices were spra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…The WHO Informal Working Group on Echinococcosis (WHOIWGE) recommends hypertonic saline 20% as the optimal protoscolicidal agent in surgery and either hypertonic saline 20% or ethyl alcohol 95% in PAIR, as these substances are effective with fewer complications [5,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The WHO Informal Working Group on Echinococcosis (WHOIWGE) recommends hypertonic saline 20% as the optimal protoscolicidal agent in surgery and either hypertonic saline 20% or ethyl alcohol 95% in PAIR, as these substances are effective with fewer complications [5,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical excision remains the preferred treatment method, and postoperative antihelminthic therapy (albendazole) is administered to prevent recurrence [14,15]. Intraoperative safety precautions involve using fields of hypertonic saline or hydrogen peroxide applied to the wound borders to reduce the risk of recurrence [16][17][18][19]. Local recurrence rates may vary, and in cases with inadequate surgical margins or intraoperative cyst rupture, as seen in this case, they could be as high as 12.4% [20].…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical procedures have shown satisfactory results in the treatment of hydatid cysts, there is a risk of developing secondary infections, with recurrence rates ranging from 2 to 25% of patients. In this context, particular attention has been paid to scolicidal agents used for intraoperative inactivation of the germinal elements of the hydatid larvocyst and determination of the eff ective exposure time [21,22]. In addition to the scolicidal substances known and used in practice [21], several recent studies have reported, as an alternative option, the use of scolicidal agents of plant origin [23,24], nanoparticles of silver, iron, copper, selenium, etc.…”
Section: -Increasing Parietal Vascular Thrombosis; D -Reminiscences O...mentioning
confidence: 99%
“…In this context, particular attention has been paid to scolicidal agents used for intraoperative inactivation of the germinal elements of the hydatid larvocyst and determination of the eff ective exposure time [21,22]. In addition to the scolicidal substances known and used in practice [21], several recent studies have reported, as an alternative option, the use of scolicidal agents of plant origin [23,24], nanoparticles of silver, iron, copper, selenium, etc. [25,26], the venom peptides of some scorpion species [27,28], although the results obtained are still in the stage of desideratum.…”
Section: -Increasing Parietal Vascular Thrombosis; D -Reminiscences O...mentioning
confidence: 99%